2021
DOI: 10.1364/ao.427755
|View full text |Cite
|
Sign up to set email alerts
|

All-optical graphene-on-silicon slot waveguide modulator based on graphene’s Kerr effect

Abstract: All-optical graphene-based optical modulators have recently attracted much attention because of their ultrafast and broadband response characteristics (bandwidth larger than 100 GHz) in comparison with the previous graphene-based optical modulators, which are electrically tuned via the graphene Fermi level. Silicon photonics has some benefits such as low cost and high compatibility with CMOS design and manufacturing technology. On the other hand, graphene has a unique large nonlinear Kerr coefficient, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The performance analysis of the proposed modulator was done using the eigenmode analysis method from the commercial photonic software of lumerical at the wavelengths of 1. 55…”
Section: Me and MDmentioning
confidence: 99%
“…The performance analysis of the proposed modulator was done using the eigenmode analysis method from the commercial photonic software of lumerical at the wavelengths of 1. 55…”
Section: Me and MDmentioning
confidence: 99%
“…Since then, several graphene integrated modulators have been proposed [70][71][72][74][75][76][77][78]. Graphene-based modulators have already demonstrate their ability to outperform traditional modulators, but there is still plenty of room for optimization [68,72,[78][79][80][81]. It has been shown that judicious design and optimization of modulators can enable their unprecedented performance [68,72,[82][83][84].…”
Section: Introductionmentioning
confidence: 99%